Role and effectiveness of surface EMG feedback in sports and orthopedic rehabilitation: a systematic review - Thomas Haab; Peter Leinen; Paul Burkey (Exploration of Musculoskeletal Diseases, 2024)
Background: The aim of the study was to conduct a literature review within the fields of sports and orthopedic rehabilitation to evaluate the efficacy of interventions incorporating electromyographic feedback (EMG FB) training compared to same interventions without EMG FB. Methods: A systematic search of three databases (PubMed, Cochrane, and Web of Science) was conducted until February 2023, without limitation on the publication date. The search strategy adhered to the PRISMA guidelines. Inclusion criteria and data extraction protocol were established a priori. The methodological quality of the included primary studies was assessed by using the PEDro scale. Results: A total of ten randomized controlled trials (RCTs; 2 in sports and 8 in orthopedic rehabilitation) involving 397 participants were included. The outcomes were categorized into three areas: 1) muscle strength and activation, 2) pain perception, and 3) functionality and joint range of motion. The quality of these studies ranges from 5 to 8 on the PEDro scale. The findings demonstrate both significant and non-significant differences between the interventions with and without EMG FB across all categories. The calculated effect sizes vary from small to large. Discussion: This review suggests that EMG FB training can be effective to enhance muscle strength, muscle control, pain reduction, functionality, and joint range of motion. The studies provide evidence for the varying impacts of EMG FB training, demonstrating both significant and non-significant outcomes across different populations and intervention types. These differences within the findings not only highlight the potential of EMG FB, but also emphasize the need for further research to identify the conditions and populations in which EMG FB is most effective.